The Covid Response: A scientist’s account of New Zealand’s pandemic and what comes next.: Shaun Hendy. 2025. Bridget Williams Books. ISBN 9781991301321 - Jull, Andrew (New Zealand Science Review, 2025)
Book Review: The Covid Response: A scientist’s account of New Zealand’s pandemic and what comes next.